Storage studies of canton-type noodles made from coconut residue flour - Bacay, Ma Christina N.; Galvez, Flor Crisanta F. (1996., 1996)
The effects of frying time (90, 150 and 120 sec) and fat content of coconut residue flour (23, 28 and 33%) on the storage behavior of canton-type noodles incorporated with coconut residue flour (CRF) were studied. The storage stability of the product was established at room temperature through moisture content determination, moisture sorption isotherm establishment, water activity analysis, microbial examination and peroxide value determination. Results indicated that the CRF noodles may be stored in cellophane bags for three months without spoilage. The microbial loads after three months of storage were still within the safe level of 10^5 cfu per gram sample. Peroxide values of the products were within 10 mEq/kg, the borderline for randicity of fats and oils. The sorption isotherms obtained where characteristic of non-hygroscopic food products. A frying time of 150 sec and 23% fat in CRF resulted in canton-type noodles that were most stable at room temperature for three months.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Coconut flour; Coconut products